What's in your 403(b)? Academic retirement plans and the costs of underdiversification - John Angus; William O. Brown; Janet Kiholm Smith; Richard L. Smith (Claremont McKenna College, Department of Economics, 2005)
Many college and university 403(b) plans restrict the menu of investment choices to funds offered by TIAA-CREF, the current manager of over half of all 403(b) contributions. Further, in the face of Internal Revenue Code changes that will take effect in 2006 and will make 403(b) plan ERISA compliance more difficult, some sponsors are dropping their existing alternatives to TIAA-CREF. Using eight years of historical performance data, we study the efficiency of the TIAA-CREF opportunity set relative to a somewhat larger set that includes several standard index funds, and we estimate the lifetime opportunity losses to participants who are constrained to invest only in TIAA-CREF. Based on efficient frontier analysis, and assuming optimal rebalancing by a loss-averse individual as time to retirement approaches, our analysis demonstrates that the opportunity losses are economically significant. Depending on loss-aversion, and diversification constraints, over a forty-year work-life an employee who is restricted to TIAA-CREF would lose approximately half of terminal wealth, compared to investing in the expanded menu that includes index funds. Moreover, limiting the choices to TIAA-CREF does not appear to help even unsophisticated investors. TIAA-CREF equity funds offer little meaningful diversification and are no less risky than the alternative index funds. Even when a naïve diversification strategy of equally-weighting (1/n) all available funds is applied, the expanded menu outperforms the restricted portfolio by about 26 percent over the employee's work-life. The findings have direct implications for the over 6.8 million enrollees in 403(b) plans, who currently make around 27 billion in annual contributions, and indirect implications for the much larger population of 401(k)-type defined contribution plans.
Keywords: G11; G23; D14; G28; G18; H24; 330; Alterssicherung; Akademische Berufe; Investmentfonds; Portfolio-Management; USA